2022
DOI: 10.21511/im.18(3).2022.17
|View full text |Cite
|
Sign up to set email alerts
|

Buy now or regret later: Social media-induced panic buying of medical supplies during COVID-19

Abstract: A huge body of research analyzed panic buying during the pandemic; however, there is a dearth of studies scrutinizing social media triggering panic buying of drugs and medical supplies. This study assesses the impact of social media on panic buying of drugs and medical supplies during COVID-19. An online survey was conducted in the Delhi-NCR region (India) using a 5-point Likert scale questionnaire. The data were collected from the respondents (N = 250) who were youngsters considering their pivotal role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Social media is significantly influencing purchasing behavior during COVID-19 (Parveen et al, 2022). The use of social media such as Instagram and Facebook is a very effective online marketing strategy (Atmaja & Verawati, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Social media is significantly influencing purchasing behavior during COVID-19 (Parveen et al, 2022). The use of social media such as Instagram and Facebook is a very effective online marketing strategy (Atmaja & Verawati, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that the typical Internet user of the twentieth century is found to be young, professional and affluent with higher levels of income and higher education (Palumbo and Herbig, 1998;Khaled, A. S et al, 2022;Almugari et al, 2022;Parveen et al, 2022;Al-Homaidi et al, 2020;Al Maqtari et al, 2020). Such an individual value time more than money and therefore the working population and dual-income or single-parent households who face time constraints are better candidates to be targeted by non-store retailers (Burke, 1997;Salah et al, 2023;.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, global mobile app revenues are projected to surpass 30 billion US dollars in the coming year (statistics portal, 2016;Khaled, A. S et al, 2022;Almugari et al, 2022;Parveen et al, 2022;Al Maqtari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%